Policy choices for the 1990s - Balassa, Bela A. (New York : New York University Press, 1993)
The book deals with some of the most important economic policy issues by Bela Balassa.
Includes bibliographical references and indexes.
rua 24/04/2017
Loans
Keywords: Economic policy; International economic integration; Economic development; International economic relations